Biofoam from The Waste of Durian Seeds and Corn Cobs - Mabela, Megawati K.; Sabang, Sri M. (Jurnal Akademika Kimia, 2023)
Biofoam is a styrofoam substitute packaging made with starch and fiber as the basic ingredients. This study aims to determine the characteristics (biodegradation test, pressure strength and water absorption) of biofoam produced from durian seed waste and corn cobs. The best treatment in this study was biofoam made using a mixture of durian seeds starch and corn cobs fiber made with 5 % NaOH concentration, where the results obtained were the water absorption test values with 1 minute, 2 minutes, and 3 minutes, namely 11.20 %, 14.22 % and 16.81 %. While the compressive strength test value obtained is 16.85 10-5 Pa, and the results of the biodegradation test are obtained at 35.42 % within 14 days of burial in the soil. The FTIR test results showed that the biofoam groups produced from a mixture of corn cob fibers with different concentrations of NaOH still showed similarities in their functional groups, where none gave rise to new peaks. The functional group content of the resulting biofoam includes the CH group (alkane) and the C. C Group (alkyne) C=C group (aromatic ring and OH group.